Risk of gene introgression from transgenic wheat to jointed goatgrass - Econopouly, Bethany F., author; Byrne, Patrick F., 1948-, advisor; McKay, John K., advisor; Funk, W. Chris, committee member; Lapitan, Nora Lyssa V., committee member (Colorado State University. Libraries, 2010)
To view the abstract, please see the full text of the document.
Department Head: Gary Peterson.